Paracrine signaling in cancer-associated fibroblasts: central regulators of the tumor immune microenvironment - Ye Li; Longyun Wang; Wenzhe Ma; Jibiao Wu; Qibiao Wu; Changgang Sun (Journal of Translational Medicine, 2025)
Abstract Despite groundbreaking advances in cancer immunotherapy, clinical efficacy remains constrained by the immunosuppressive tumor microenvironment (TME). As key stromal components within this TME, cancer-associated fibroblasts (CAFs) emerge as pivotal regulators of drug resistance and immune evasion. Beyond establishing physical barriers that exclude cytotoxic T cells from tumor nests, that is creating an immune “desert”, CAFs dynamically reprogram the TME through multifaceted paracrine signaling, orchestrating crosstalk among tumor cells, stromal components, and immune cells. The complex paracrine signaling network jointly promotes the recruitment of immunosuppressive cells, alters the dynamics of immune cells, remodels the extracellular matrix, and ultimately establishes the immunosuppressive TME. Emerging strategies aimed at undermining the paracrine signaling Network of CAF-TME have shown potential in clinical studies to enhance the response to immunotherapy. Natural compounds such as curcumin and Baicalein and their derivatives have further expanded therapeutic approaches by regulating the paracrine phenotype of CAF due to their inherent multi-target intervention advantages. This review describes CAF and its paracrine effect as the central regulators of TME immunosuppression, emphasizing its key role in the immunotherapy response and providing new possibilities for clinical treatment strategies to restore CAFs paracrine-mediated immunosuppression and improve the efficacy of immunotherapy.